Otoritas dan Gerakan Keagamaan Daengguru: Studi Sejarah Islamisasi di Sulawesi Selatan - Mustari Bosra (FALASIFA : Jurnal Studi Keislaman, 2020)
This paper is about the Islamization movement of the kingdoms in South Sulawesi, sointegrated sara 'is into a social institution called pangadereng (Bugis) angadakkang (Makassar). To ensure the upholding of Islamic law, which has been integrated into the social system, a religious bureaucracy (Islam) known aswas formed sara '. The royal bureaucratic officials who handle this institution, from the central level to the village or village level are called parewa sara ', which in this study uses the term daengguru. This integration pattern was developed in almost all Islamic kingdoms in South Sulawesi. Adat has its own field and sharia controls its own field. One another should not disturb each other. When the King of Bone La Maddarremmeng was about to confront Islam and customs, he was opposed by all parties. When Arung Matowa Wajo declared a strong Islamization, he was also evicted from his position.